2016
DOI: 10.5937/ekonomika1604115g
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability of companies in the Republic of Serbia: Empirical research

Abstract: In an era of constant change in all spheres of business, an essential factor in the survival of a company is monitoring developments in the region, rapid response to current trends and anticipating future market developments. In this way, companies become more successful and have more proactive control of their future. The aim of paper was that through empirical research, did on the model of Denison, shows the degree of adaptability of enterprises in the Republic of Serbia, to identify the factors that influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Research on the adaptability of companies in the Republic of Serbia [14] has shown that the average adaptability grade is 3.50 which is the value slightly higher than grade 3 described as "neither agree nor disagree" and lower than grade 4 described as "mostly agree". This shows that companies in Serbia should work on the adaptability in all business areas in order to respond to changes in a better way.…”
Section: Strategic Management In the Function Of Competitivenessmentioning
confidence: 81%
See 1 more Smart Citation
“…Research on the adaptability of companies in the Republic of Serbia [14] has shown that the average adaptability grade is 3.50 which is the value slightly higher than grade 3 described as "neither agree nor disagree" and lower than grade 4 described as "mostly agree". This shows that companies in Serbia should work on the adaptability in all business areas in order to respond to changes in a better way.…”
Section: Strategic Management In the Function Of Competitivenessmentioning
confidence: 81%
“…Generally speaking, most authors agree on the four main pillars of competitiveness: quality, innovations, customer relationship and the economics of scale [16]. This is why it can be said that an organization that in the 21 st century brags about its consistency in doing business, commonality of its products or status quo, is more in the period of stagnation than that it is successful and stable [17].…”
Section: Strategic Management In the Function Of Competitivenessmentioning
confidence: 99%